2003
DOI: 10.1109/jlt.2003.816889
|View full text |Cite
|
Sign up to set email alerts
|

Variable optical attenuator fabricated by direct uv writing

Abstract: Abstract-It is demonstrated that direct ultraviolet writing of waveguides is a method suitable for mass production of compact variable optical attenuators with low insertion loss, low polarization-dependent loss, and high dynamic range. The fabrication setup is shown to be robust, providing good device performance over a period of many months without maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The experimental setup is similar to that used in earlier work [3], except for the fact that the scanning accuracy has recently been improved by means of interferometric position feedback [6]. The UV beam has a wavelength of 257 nm and may be blocked using a shutter as required in the scanning process.…”
Section: Device Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental setup is similar to that used in earlier work [3], except for the fact that the scanning accuracy has recently been improved by means of interferometric position feedback [6]. The UV beam has a wavelength of 257 nm and may be blocked using a shutter as required in the scanning process.…”
Section: Device Fabricationmentioning
confidence: 99%
“…In this technique, waveguides are written directly into a photosensitive glass sample with a focused UV laser, thereby avoiding expensive photolithographic and etching-based fabrication steps. Up to date, the only demonstration of a commercially interesting UV written device is a variable optical attenuator [3], which has a limited complexity of the layout. In this letter, the development of compact, low loss, uniform, and broad-band 2 8 optical splitters by means of direct UV writing is reported.…”
mentioning
confidence: 99%
“…Direct UV writing [5] is a fabrication technique, where highperformance waveguides are written directly into a planar glass sample with a focused UV laser beam; hence, it does not require photolithography and is well suited for rapid prototyping. The technology was originally developed for low-cost telecom applications such as variable optical attenuators [6]. Recently, UV writing has been employed for fabrication of devices with increased complexity, such as multichannel optical power splitters [7], [8] and broadband directional couplers [9].…”
Section: Introductionmentioning
confidence: 99%
“…This process avoids the use of costly photolithographic and etching based fabrication steps and does not require a cleanroom. We have previously shown that direct UV writing can be a stable platform for production of high performance components such as variable optical attenuators [2], return-to-zero signal generators [3] and broadband directional couplers [4].…”
Section: Introductionmentioning
confidence: 99%